A MUSICAL ANALYSIS OF "WATU PINAWETENGAN" BY YUDI NOVRIAN KOMALIG: PROGRAM MUSIC BASED ON MINAHASANESE FOLKLORE FOR STRING QUARTET AND TAMBOUR - YUDI NOVRIAN KOMALIG (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2020)
Watu Pinawetengan is a program music that attempts to render an extra-musical narrative musically which material comes from the Minahasa folklore about the Watu Pinawetengan mandate. The story is about negotiations in dividing agricultural territories to reduce conflicts due to land grabs. The existence of the values of deliberation, tolerance, and the spirit of unity are the reasons this story was appointed as a musical composition. So it is necessary to find relevant musical ideas to realize this composition. The process of creation begins by assigning extramusical material. This is done by gathering information and developing ideas about the plot. After that the musical elements are arranged based on the existing extramusical material. Minahasa ethnic music idioms such as scales, ornaments, and intervals are used to present the Minahasa ethnic atmosphere. Whereas Western diatonic music idioms help to create supporting atmosphere such as conflict, tension, concern, joy, and the spirit of unity.